Successful Retrieval of a Dismembered Central Venous Catheter Stuck to the Right Pulmonary Artery Using a Stepwise Approach - Keisuke Nakabayashi; Hidekimi Nomura; Daichi Isomura; Ryo Sugiura; Toshiaki Oka (Case Reports in Cardiology)
Recent advances in anticancer chemotherapy have resulted in an increase in the number of patients requiring a central venous port catheter, and the incidence of catheter pinch-off syndrome has been increasing. Catheter pinch-off syndrome is a rare and unusual complication. It is difficult to retrieve dislodged catheters from the pulmonary artery, especially if the catheter is stuck to the peripheral pulmonary artery. We herein describe the successful removal of a catheter stuck in the pulmonary artery with a stepwise approach. First, a pigtail catheter was used to tug the dislodged catheter in order to free the unilateral end. Then, a gooseneck snare was used to catch and pull the catheter out of the patient. The key to success is to free the end of the catheter.